Traction Calculation for Metro B-cars - Ye, Likai (Journal of Theory and Practice of Engineering Science, 2024)
Traction calculation of urban rail transit vehicles is an important means to confirm the traction quality, running speed, running time and energy consumption, and it can also improve the safety of subway operation. In this paper, the train control system is introduced, and the basic train resistance, train traction characteristics, train regenerative braking characteristics, train comprehensive braking characteristics model and simulation calculation model are established.